Examining native CSR advertising as a post-crisis response strategy. Issue 2 (17th February 2022) - Wu, Linwan; Overton, Holly
Abstract: Although companies have started to adopt native CSR advertising for crisis communication, no existing research has examined this new phenomenon. To fill the gap, this study tested how crisis type and ad identification influence the effectiveness of native CSR advertising as a post-crisis response strategy. An online experiment was conducted using a nationally representative sample of U.S. adults. The results indicated that perceived manipulativeness was the underlying mechanism of how ad identification impaired consumer responses. Crisis type affected advertising effectiveness through consumers' attributions of crisis responsibility and values-driven CSR motive. More importantly, ad identification significantly impaired consumers' attitudes toward a native CSR advertisement and their intention to share the advertisement in the victim crisis condition, but not in the accidental or intentional crisis condition. These findings provide meaningful contributions to both the research and practice of CSR advertising.